Examining Gender Differences in Slang Usage Among Gen Z and Millennials in Surabaya - Jihan, Fatima (Language Horizon: Journal of Language Studies, 2024)
This study investigates the differences in language use and politeness norms between Millennials and Generation Z. Through a mixed-methods approach combining surveys and interviews, the research examines how digital communication and cultural shifts influence these generations’ communication styles. Findings reveal Generation Z’s frequent use of slang and direct, inclusive communication, contrasting with Millennials’ more reserved approach, especially in professional settings. The study highlights the importance of understanding these differences for effective intergenerational communication and suggests educational programs, workplace training, and digital literacy enhancement as strategies to bridge generational gaps. By promoting adaptability and inclusivity, these recommendations aim to foster a cohesive and understanding society.